Sedimentation of inclusions in melts of aerospace structural aluminium alloy castings: a sustainable approach - Sivarupan, Tharmalingam; Jayaraman Palanivel, Arul; Georgarakis, Konstantinos; Forde, John; Rawding, Joseph; Shaw, Ben; Salonitis, Konstantinos; Jolly, Mark R. (Springer, 2025)
Achieving the full potential of mechanical and other properties in aerospace structural aluminium alloy castings is often hindered by the presence of detrimental inclusions in the melt during casting. The inclusions arise from high-temperature chemical reactions and the dissolution of substances in contact with the melt or pre-existing in the alloy. Suitable additions to the melt can precipitate on the inclusions and cause them to sediment, resulting in cleaner melt. Simulation techniques were employed with commercial software packages (Flow3D) using high-performance cluster computing (HPC) facilities to analyse the behaviour of impurity particles of various sizes and distributions under different boundary conditions such as temperature, pressure, flow rate, and heat transfer. The simulations provide insights into the sedimentation process to identify effective methods for eliminating/reducing these particles from the melt. Some of the practical melt holding or processing challenges, and mitigations, are also discussed.